The enduring value of Roger Murray - Johnson, Paul 1960-; Sonkin, Paul D. 1968- (Heilbrunn Center for Graham & Dodd Investing Series, 2023)
Roger Murray (1911-1998) was a crucial figure in the history of value investing. A financial professional, economist, adviser to members of Congress, and educator, Murray was the successor to the legendary Benjamin Graham as professor of the securities analysis course at Columbia Business School. There, he mentored generations of students, including Mario Gabelli, Charles Royce, Leon G. Cooperman, and Art Samberg.This book offers a compelling account of Murray's multifaceted career alongside a series of remarkable lectures he gave late in his life that encapsulated his philosophy of investing. The investing professionals and educators Paul Johnson and Paul D. Sonkin chronicle Murray's life and accomplishments, capturing his professional triumphs, theoretical insights, and lasting legacy. They highlight Murray's educational philosophy and mentorship, including personal recollections from his students about his teaching and influence.The Enduring Value of Roger Murray features the transcripts of four lectures Murray gave in 1993, hosted by Gabelli, which became legendary in the investing community. These lectures inspired Bruce Greenwald to ask Murray to co-teach a security analysis course, leading to the resurrection of value investing education at Columbia Business School, which had waned after Murray's retirement in 1977. Annotated by Johnson and Sonkin, these lectures are now available to a wide audience for the first time. They will be illuminating and instructive for all value investing students and practitioners today.